Kepemimpinan Spritual Guru PAI pada Masa Pandemi Covid-19 - Sulaiman Sulaiman (STAIFAS-Press, 2021)
The leadershipteachers of Islamic Religious Education during the Covid-19 pandemic has an effect in every area of ​​Indonesian people's life, one of the sectors is the world of education. Education in Indonesia seems to get a shock that creates a new order in the learning process. The implication is that the learning process becomes distance learning, inevitably it must be applied considering the Ministry of Education and Culture's instructions to continue learning in the midst of the Covid-19 outbreak. Teachers at all levels of education are required to make new learning plans related to Distance Learning, which has never been implemented before. From the limitations of Islamic Religious Education teachers at the junior high school level who in fact are accustomed to face-to-face learning, they must turn learning into distance learning. Teachers of Islamic Religious Education at the primary school, primary school and and tertiary levels have a significant impact on the aspects of distance / online / online learning, as a respondent the author turned out to have an advantage in preparing for the learning process during the Covid-19 period. In distance learning they are able to continue working by optimizing all the potential that exists through electronic media. difficulty and also ease in implementing distance learning cannot be avoided, considering that the distance and access of students in following the learning process does not go as desired. This is also an attraction for research related to the distance learning process in schools.